Interview - "Mental Health in Nicaragua" - Vogelman, Lloyd (PINS-Psychology in Society, 2025)
Lloyd Vogelman in discussion with psychiatrist Dr. Sequeira is Director of the psychiatric hospital in Managua and also head of the mental health training programme in Nicaragua. Nicaragua is a country which has had a long history of dictatorial rule. The last of the great dictators, Somoza, fell in the 1979 revolution. Despite the efforts of the Sandinistas in attempting to improve the quality of life through various social programmes, increased political participation, and a better distribution of wealth, 36 000 people have died, been injured or disappeared since 1979. The primary cause of death has been the war against the Contras. Almost all Nicaraguans have lost someone close to them.